1991
DOI: 10.1111/j.1365-2621.1991.tb08620.x
|View full text |Cite
|
Sign up to set email alerts
|

Processing Ingredients Affecting Oxidative and Textural Stability of Restructured Beef Roasts

Abstract: Restructured beef roasts containing 0.3% sodium tripolyphosphate (SIT) and 1% soy protein isolate (SPI); or STP only; or SPI only; or no STP or SPI were cooked at 70 or 100°C to an internal temperature of 65"C, then stored at 4°C for 0 and 3 days. In control roasts, the higher cooking temperature resulted in higher (p 5 0.05) TBA values. STP and SPI inhibited oxidation but the effect was not detected sensorially. Significant interactions (p 5 0.05) indicated that STP was more effective at higher cooking temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…Arganosa et al (1991) reported lower cook yield and correspondingly lesser moisture content of the cooked samples at 100°C than at 70°C. Vasanthi et al (2007) and Combes et al (2003) reported higher cooking loss with the increasing cooking time.…”
Section: Product Yieldmentioning
confidence: 93%
See 1 more Smart Citation
“…Arganosa et al (1991) reported lower cook yield and correspondingly lesser moisture content of the cooked samples at 100°C than at 70°C. Vasanthi et al (2007) and Combes et al (2003) reported higher cooking loss with the increasing cooking time.…”
Section: Product Yieldmentioning
confidence: 93%
“…Huffman et al (1981) reported increase in cook yield with increase in salt level and phosphate level for restructured pork chops. Lower cook yield and correspondingly lower moisture of the cooked samples were obtained at 100°C than at 70°C (Arganosa et al 1991). Highly acceptable restructured chicken block was developed with incorporation of gizzard and fat and with shelf life of 10 days under refrigerated storage condition (Sudheer et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Arganosa, Godber, Tanchotikul, McMillin, and Shao (1991) found it was unexpected that at 1008C STP treated roasts had highest shear force, as others have found that phosphates reduced shear values in reheated wholemuscle beef roasts (Paterson & Parish, 1988). Because of the adverse effect that higher cooking temperature had on cook yield and moisture attributes, at higher cooking temperature a higher shear value was obtained (Arganosa et al, 1991). Arganosa et al (1991) also indicated that STP was more effective on oxidation inhibition at higher cooking temperatures and soy protein isolate (SPI) at lower temperatures.…”
Section: Cookingmentioning
confidence: 96%
“…Because of the adverse effect that higher cooking temperature had on cook yield and moisture attributes, at higher cooking temperature a higher shear value was obtained (Arganosa et al, 1991). Arganosa et al (1991) also indicated that STP was more effective on oxidation inhibition at higher cooking temperatures and soy protein isolate (SPI) at lower temperatures. In general, cooking was not drawing more attention in recent decades.…”
Section: Cookingmentioning
confidence: 99%
“…Restructured meat products have advantages such as compositional control, convenient preparation and economical production. Therefore, these products can be formulated to meet specific consumer needs (Akamittath et al 1990;Arganosa et al 1991). Nevertheless, there are some major concerns associated with precooked restructured beef products, which include both lipid and cholesterol oxidation (Arganosa et al 1991;Rankin and Pike 1993).…”
Section: Introductionmentioning
confidence: 99%